2010
DOI: 10.1103/physreve.81.027201
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude death in nonlinear oscillators with nonlinear coupling

Abstract: Amplitude death is the cessation of oscillations that occurs in coupled nonlinear systems when fixed points are stabilized as a consequence of the interaction. We show here that this phenomenon is very general: it occurs in nonlinearly coupled systems in the absence of parameter mismatch or time delay although time-delayed interactions can enhance the effect. Application is made to synaptically coupled model neurons, nonlinearly coupled Rössler oscillators, as well as to networks of nonlinear oscillators with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 26 publications
2
79
0
Order By: Relevance
“…8 is the largest two Lyapunov exponents for identical oscillators as a function of ε, the region where all Lyapunov exponents are negative corresponds to amplitude death (the transients are shown in the inset). We have found that the phenomenon of amplitude death when systems are coupled through nonlinear interactions is very general and occurs in the absence of parameter mismatch, in the absence of time-delay (although time delay can enhance the effect) [15,76].…”
Section: Nonlinear Couplingmentioning
confidence: 99%
See 4 more Smart Citations
“…8 is the largest two Lyapunov exponents for identical oscillators as a function of ε, the region where all Lyapunov exponents are negative corresponds to amplitude death (the transients are shown in the inset). We have found that the phenomenon of amplitude death when systems are coupled through nonlinear interactions is very general and occurs in the absence of parameter mismatch, in the absence of time-delay (although time delay can enhance the effect) [15,76].…”
Section: Nonlinear Couplingmentioning
confidence: 99%
“…An interesting extension that uses nonlinear coupling makes it possible to not only achieve AD, but also to specify the steady state of the coupled system [15,21]. We will illustrate the targeting of specific fixed points in Sec.…”
Section: Nonlinear Couplingmentioning
confidence: 99%
See 3 more Smart Citations